Meaning and the dynamics of interpretation : selected papers of Hans Kamp / Klaus von Heusinger; Alice G B ter Meulen; Hans Kamp - Heusinger, Klaus von
This selection of research papers written by Hans Kamp presents the core of his scientific research on natural language semantics and its relation to logic, philosophy and linguistics. Arranged in six sections, the topics range from philosophical reflection on the foundational issues in the ancient Sororites Paradox with a formal account of its solution, to a detailed account of presuppositions in dynamic semantics.